Carbon Nanotubes: Simple Salt‐Coordinated n‐Type Nanocarbon Materials Stable in Air (Adv. Funct. Mater. 18/2016). (May 2016) - Nonoguchi, Yoshiyuki; Nakano, Motohiro; Murayama, Tomoko; Hagino, Harutoshi; Hama, Shota; Miyazaki, Koji; Matsubara, Ryosuke; Nakamura, Masakazu; Kawai, Tsuyoshi
Abstract : Y. Nonoguchi, T. Kawai, and co‐workers prepare high‐stability carbon nanotube structures that behave as n‐type conductors on page 3021. Single‐walled carbon nanotubes are converted to n‐type conductors by doping with salt‐crown ether complexes. The material demonstrates unprecedented durability in air even at raised temperatures, an essential requirement in thermoelectric applications.